A Subjective Evaluation of Texture Synthesis Methods. (23rd May 2017) - Kolář, M.; Debattista, K.; Chalmers, A.
Abstract: This paper presents the results of a user study which quantifies the relative and absolute quality of example‐based texture synthesis algorithms. In order to allow such evaluation, a list of texture properties is compiled, and a minimal representative set of textures is selected to cover these. Six texture synthesis methods are compared against each other and a reference on a selection of twelve textures by non‐expert participants (N = 67). Results demonstrate certain algorithms successfully solve the problem of texture synthesis for certain textures, but there are no satisfactory results for other types of texture properties. The presented textures and results make it possible for future work to be subjectively compared, thus facilitating the development of future texture synthesis methods.